STUDI KASUS PENERAPAN VENDOR MANAGED INVENTORY PADA SISTEM RANTAI PASOK - Ricky Virona Martono (Jurnal Manajemen Industri dan Logistik (JMIL), 2018)
Vendor Managed Inventory (VMI) is an approach in managing inventory between supplier and consumer in an supply chain system. In VMI concept, supplier keeps its inventory at consumer’s warehouse, meanwhile inventory ownership belong to supplier until it is used by consumer. The advantage of VMI is to reduce inventory replenishment ordering process and to reduce the usage of consumer’s warehouse space. Some key factors to achieve VMI success are: coordination, communication, production system and inventory order reliability.When supplier is a subsidiary of consumer, coordination between the two usually puts them not at an equivalent level, especially when supplier’s infrastructure is not as good as that at consumer. This research is a case study at a pharmaceutical company and its supplier which acts as its subsidiary. Information and data gathered by deep interview to all parties responsible for supply chain, production, and inventory at supplier and consumer sides. The results show advantages and obstacles in applying VMI, thus long-term commitment is needed to reach a better performance.